DEMOCRATIC PARTY TOWARDS THE YUGOSLAV AND KOSOVO QUESTION 1990–1991 (Heritage, 2025)
The Democratic Party was revived in 1990 on similar values ​​to the interwar party of the same name, banned after World War II. The renewed party's newspaper, again inspired by the party's newspaper immediately after the war, was called Demokratija. The party's program documents envision the survival of the Yugoslav state as the most expedient political framework for the Serbian people, who would continue to live in a single state, necessarily politically and economically reformed in the image of Western democracies, but not its survival at all costs. In the event of its disintegration, the party proposed the territorial unification of the Serbian people. Despite this, it did advocate an anti-war policy and cooperated with various factors in the country and abroad in this regard. However, there were also major differences in the positions of the party leaders themselves regarding the Yugoslav crisis, which led to factions and the creation of new parties. There were no such divisions regarding the Kosovo issue, but rather a near-consensus that Albanians could enjoy cultural and educational autonomy modeled after contemporary European solutions and that they too would find a place in the future democratized Serbia advocated by the party. However, there was a somewhat naive expectation that Albanians would seek a solution beyond republican status or independence. During 1990, the party introduced itself in Kosovo, and in 1991, it formed a series of committees, of which the Pristina one was the strongest and most active. However, its Kosovo membership was too small to threaten the communist and socialist government at all. Its work was limited to criticizing the government for betraying national interests, incompetence, and corruption. The party, within the broader Yugoslav model, proposed privatization as a framework for solving the accumulated economic problems in Kosovo, but also more active diplomacy as a response to Albanian activities aimed at internationalizing the problem.
Keywords: Democratic Party, Demokratija newspaper, Serbian intellectuals, breakup of Yugoslavia, Kosovo and Metohija, Yugoslav issue, Kosovo issue.